Implementation of a Lean Manufacturing Approach to Improving Productivity in SMEs: A Case Study in a Cloth Manufacturing Company - Ramasu, T.K.; Kanakana-Katumba, M.G. (The South African Journal of Industrial Engineering, 2025)
This study explored the implementation of a lean manufacturing approach to enhance productivity in small and medium-sized enterprises, focusing on a cloth manufacturing company as a case study. The objectives of this approach were to improve production efficiency and to minimise waste while ensuring a clean and safe working environment for employees. The methods used include 5S principles to help eliminate waste production in the form of rejects and reworks and assembly line balancing, with a particular emphasis on improving operational efficiency. The largest candidate rule method yielded significant improvements, reducing the number of workstations from 12 to 4, achieving an efficiency of 87.5%, and lowering the smoothing index to 22.05 compared with the existing system’s 29.17% efficiency and 147.78 smoothing index. These findings underscore the potential of lean strategies to optimise production processes and reduce inefficiencies. The study recommends that the company consistently capture, analyse, and monitor key performance indicators to track progress, ensure transparency between management and employees, and sustain growth driven by lean practices. This case study highlights the transformative impact of lean manufacturing on SME productivity and operational excellence.